Kultur in Vitro Anggrek Hitam (Coelogyne pandurata Lindl.) pada Media Murashige and Skoog dan Media Vacin Went - Fortuna, Sonia Elizabeth; Rambitan, Vandalita Maria Magdalena; Herliani, Herliani (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
Black orchid (Coelogyne pandurata Lindl.) is a typical Borneo plant that grows wild in the forest. Kersik Luway Nature Reserve, West Kutai, East Kalimantan, is one of the habitats of this plant. Frequent forest fires and the difficulty of breeding cause the scarcity of this plant. The solution is to do in vitro culture using black orchid leaf explants. The purpose of this study was to determine the differences in black orchid growth through tissue culture on MS and VW media. The media used were MS, MS + 2,4-D, VW, and MS + VW media with 6 replicates, so there were a total of 24 samples. This type of research is an experiment conducted in the laboratory. Data from observations for 10 weeks were analyzed using the chi-square test. The results of observations for 10 weeks showed that there was no callus growth. Based on the chi-square test calculation, the value of the significant level < chi count (0.05 < 0.92), there is no significant difference in the growth of black orchids through tissue culture on all media. MS and MS + VW media had the most shrinkage (6 explants). MS + 2,4-D media had the most yellowing (2 explants). MS and MS + 2,4-D media experienced the most root growth (2 explants). Overall the best media is MS media.